DEVELOPMENT OF AN INTELLIGENT EGG INCUBATOR SYSTEM BASED ON ARDUINO - Alisher Khamroev (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Artificial incubation systems play a crucial role in modern poultry farming by ensuring stable environmental conditions for embryo development. This study presents the design and implementation of an intelligent egg incubator based on the Arduino microcontroller platform integrated with environmental sensors and automated control mechanisms. The proposed system monitors temperature and humidity in real time and automatically regulates heating, ventilation, humidity generation, and egg turning processes. A real-time clock module ensures scheduled egg rotation, while IoT integration enables remote monitoring. Experimental results demonstrate improved environmental stability and increased hatchability compared to manual incubation methods. The developed system provides a low-cost, energy- efficient, and scalable solution.